(untitled) (Communications in Computational Physics, 2007)
Ab initio calculations of dielectronic recombination (DR) processes from the ground state 1s2 of He-like argon ion through doubly excited states 1s2snl, 1s2pnl(n=2 to 9) of Li-like argon ions are performed using the multi-configuration Hatree-Fock method with relativistic correction. The theoretical method and its corresponding computation will be outlined. For higher doubly excited states with n>9, the scaling law is used to extrapolate the Auger and radiative transition rates. The total and state-to-state cross sections with corresponding rate coefficients in the temperature from 102eV to 106eV are presented, as well as the DR strengths for all the separate resonances. Moreover, peculiarities of the DR from doubly excited 1s2s3l ' configurations are analyzed and the contributions of two-electron-one-photo (TEOP) radiative transitions to the DR cross sections are also investigated, such as 1s2s2 → 1s22p, due to the strong configuration interactions. Our theoretical results appear to be in excellent agreement with the previous and recent experimental measurements.